A56 THE USE OF HIGH VOLUME PLASMAPHARESIS IN ACUTE LIVER FAILURE. (26th February 2020) - Tam, L; Sy, E; Karvellas, C J
Abstract: Background: Acute liver failure (ALF) can result in irreversible shock, cerebral herniation or development of multiple organ failure (MOF). One randomized study and a separate case series have demonstrated the safety and potential improvement in transplant-free survival with the use of high volume plasmapheresis (HVP). HVP is defined as an exchange of 8-12L or 15% of ideal body weight with fresh frozen plasma. In ALF, cytokines are responsible for the progression of MOF and HVP removes these cytokines from the systemic circulation. We report a case of implementing HVP in an adult with ALF in the intensive care unit (ICU) at a tertiary care center. Aims: This case and the associated literature review highlight the value of HVP in ALF. Methods: Case report and literature review. Results: We report a case of a 34-year-old male who presented in ALF secondary to unknown ingestion. He was admitted to the ICU for worsening transaminitis, coagulopathy, hepatic encephalopathy, renal failure and hemodynamic instability which required vasopressor and ventilatory support. A discussion was made with hepatologists at a regional transplant center for potential consideration of either transplant or Molecular Adsorbent Recirculating System (MARS) therapy. However, the patient was too hemodynamically unstable for transport and also began to develop signs of cerebral edema. As a result, they recommended a trial of high volume plasmapheresis. Shortly after initiation, the patient's hemodynamic, respiratory, and biochemical parameters began to improve, resulting in less vasopressor and ventilator support (Table 1). Despite improvements in these parameters, the patient's cerebral edema continued to worsen and an electroencephalogram showed signs of a very low likelihood of functional neurological recovery. Given the overall picture, the patient's spouse decided to withdraw care. Conclusions: Presently, liver transplantation remains the only definitive management strategy for ALF patients, but many do not survive to liver transplant or are not candidates for medical or psychosocial reasons such as with this case. As a result, this case demonstrates the potential benefits of conducting HVP in centers without access to MARS or transplantation. However, although HVP did improve certain parameters for this patient, it did not improve overall prognosis. This suggests that prognosis may not improve once a certain threshold of MOF develops. Therefore, in this case and the associated literature review the optimal timing of initiating HVP remains unclear. Funding Agencies: None